Prevalence and distribution of peripheral musculoskeletal manifestations in spondyloarthritis including psoriatic arthritis - López-Medina, Clementina (2021)
Objectives: To characterise peripheral musculoskeletal involvement in patients with spondyloarthritis (SpA) including psoriatic arthritis (PsA), across the world. Methods: Cross-sectional study with 24 participating countries. Patients with a diagnosis of axial SpA (axSpA), peripheral SpA (pSpA) or PsA according to their rheumatologist were included. The investigators were asked which diagnosis out of a list of six (axSpA, PsA, pSpA, inflammatory bowel disease-associated SpA, reactive arthritis or juvenile SpA (Juv-SpA)) fitted the patient best. Peripheral manifestations (ie, peripheral joint disease, enthesitis, dactylitis and root joint disease), their localisation and treatments were evaluated. Results: A total of 4465 patients were included (61% men, mean age 44.5 years) from four geographic areas: Latin America (n=538), Europe plus North America (n=1677), Asia (n=975) and the Middle East plus North Africa (n=1275). Of those, 78% had ever suffered from at least one peripheral musculoskeletal manifestation; 57% had peripheral joint disease, 44% had enthesitis and 15% had dactylitis. Latin American had far more often peripheral joint disease (80%) than patients from other areas. Patients with PsA had predominantly upper limb and small joint involvement (52%). Hip and shoulder involvement was found in 34% of patients. The prevalence of enthesitis ranged between 41% in patients with axSpA and 65% in patients with Juv-SpA. Dactylitis was most frequent among patients with PsA (37%). Conclusion: These results suggest that all peripheral features can be found in all subtypes of SpA, and that differences are quantitative rather than qualitative. In a high proportion of patients, axial and peripheral manifestations coincided. These findings reconfirm SpA clinical subtypes are descendants of the same underlying disease, called SpA.